Excess Demand, Unemployment, Vacancies, and Wages - Hansen, Bent (Quarterly Journal of Economics, 1970)
I. A neoclassical macro theory for money wage changes, 2. — II. Neoclassical wage theory with spontaneous wage change and additional wage determinants, 3 — III. Vacancies and unemployment and excess demand, 5. — IV. The derivation of the Phillips relation, 8. — V. The form of the Phillips relation, 11. — VI. The cyclical characteristics of unemployment and vacancies, 17. — VII. Vacancies, unemployment, and equilibrium, 21.